Localized alveolar osteitis: the role of suture technique following disimpaction of mandibular third molars in a Nigerian Teaching Hospital - Thomas Owobu; Auwal S. Balarabe; Sylvester Nwabueze; Babatunde O. Bamgbose (DiscoverSys Inc., 2019)
Objective: The formation of localized alveolar osteitis following mandibular third molar disimpaction is a result of a complex interaction between systemic factors, local infection and surgical trauma. This study evaluates the relationship between wound closure techniques in the development of localized alveolar osteitis (Dry Socket) following disimpaction of mandibular third molar teeth in Aminu Kano Teaching Hospital.Material and Methods:Â A total of 120 patients between the ages of 18 and 45 years were recruited into the study. A gender ratio of male to female, 1,07 :1, was recorded.Â They were then divided into two groups (A & B) according to wound closure technique used.Â Group A had suture-less/partial wound closure and Group B had complete wound closure technique. Data were analyzed using SPSS version 20.0 (SPSS Inc, Chicago IL), with simple descriptive statistics and the X2 text, as appropriate. P < .05 was considered significant.Results: A total number of 23 patients (7.2%) developed localized alveolar osteitis from both groups. The prevalence of localized alveolar osteitis was higher in patients who received suture-less/partial wound closure technique (91.3%), while (8.7%) developed dry socket in complete wound closure technique. The difference between the two group was statistically significant (p<0.05).Conclusion: This study revealed that wound closure technique following disimpaction of mandibular third molar teeth is a major factor in the development of localized alveolar osteitis.